Study of Dried and Calcinated Ceria Stabilized Zirconia Microspheres Morphology by Small-Angle X-Ray Scattering and Optical Microscopy - A. Patriati; A. Insani; N. Suparno; E. Hutamaningtyas; S. Soontaranoon; M Mujamilah (Atom Indonesia, 2021)
The knowledge of how to avoid crack at high temperature is crucial in fuel fabrication for Experimental Power Reactor or Reaktor Daya Eksperimental (RDE). This knowledge should be established and well-mastered by BATAN. RDE uses uranium dioxide as its nuclear fuel. However, uranium utilization for research purposes is heavily restricted. Therefore, the fabrication of ceria-stabilized zirconia (CSZ) microspheres as nuclear fuel surrogate was studied. In this work, the CSZ was prepared by external gelation with two different washing solutions, i.e. isopropyl alcohol (IPA) and propylene glycol methyl ether (PGME). The morphology in nano- and micro-scale of each CSZ microspheres from both variations was evaluated by small-angle x-ray scattering (SAXS) and optical microscopy. The morphology of the CSZ microsphere after drying at 80 °C and calcination at 200 °C were observed to understand the structural change in those steps and to see the potential crack based on its morphology. There are two parameters that can prevent microspheres from cracking at high temperatures for the next process, i.e., porosity and gel texture. It was observed that IPA solution has a benefit as a washing solution as it can trigger more porosities in the microspheres, but less in gel texture.